Developing An Effective Microbial Community As Bioinoculant For Enhanced Productivity Of Tomato (Lycopersicon Esculantum Mill.) With Improved Soil Fertility (International Journal of Food and Nutritional Sciences, 2022)
The efficacy of a consortium of seven plant growth promoting micro-organisms immobilized in a mixture of talc and gluten (3:1 ratio) was investigated for its effect on growth and productivity of Lycopersicon esculantum Mill. in a pot experiment. The shoot length (58.08 %), root length (104.8 %t), shoot fresh and dry biomass (97.4 % and 159.1 %), and root fresh and dry biomass (202.8% and 212%) were found significantly higher in carrier based bioformulation (T1) as compared to control (T5). After inoculation of this novel microbial bioformulation, it also increased fruit number (148.3%) and fruit biomass (195.3%) as compared to the untreated control. Furthermore, post-harvest study of this bioformulation treated soil showed improvement in organic matter (57.8%), available nitrogen (285%), phosphorus (972.7%), potassium (99.2%) and enzyme activities like microbial biomass carbon (224.0%) and alkaline phosphatase activity (420.6%) as compared to pre-plantation soil. The root colonization of microbes, as evident by scanning electron microscopy was also increased. Our results demonstrated that talc+gluten-based bioformulation with the consortium of seven agriculturally beneficial soil microbes significantly enhance the soil fertility and tomato yield. Therefore, the study concluded that, this bioformulation can act as a promising substitute of chemical fertilizers for the economic and ecological benefits in the tomato cultivation.